Formação e autonomia do professor universitário: um estudo na Universidade Federal de Goiás - Resende, Maria do Rosário Silva (2005)
ABSTRACT This research focuses on the formation and autonomy of the university professor. A critique of reason has been presented as a requirement for the formation of a truly autonomous individual. Psychological and educational perspectives were the basis for this paper. The Federal University of Goiás was used as the empirical research field in which the formation of its professors and the possibilities for autonomy in their everyday relations within this institution were investigated. The central hypothesis, which has been formulated is that in Federal Universities the objective day-to-day working conditions of the professor affect their performance, their teaching activities, their autonomy, their awareness and self-criticism. These conditions often represent one more obstacle for the expression of the professor s individuality and consequently of his autonomy, even that which is formally admitted. These objective working conditions interfere in such a way that they frequently cause professors to develop behavioral patterns of acceptance, resignation, apathy and adjustment when faced with these day-day-day situations. A questionnaire was used to collect the information essential for the objectives and verification of the hypotheses in the research. The information collected from the questionnaires underwent both a statistical analysis using the SPSS program, and an analysis of content. The critical theory of society, developed by Horkheimer, Adorno e Marcuse, is the theoretical support for the paper. An attempt was made to check out the influence of the changes taking place in Brazilian Federal Universities and the objective working conditions of these professors, partly resultant from official educational policies. The sample is made up of 419 permanent professors at the Federal University of Goiás. All have doctorates and full time contracts and are working in undergraduate departments. For this sample only 56 professors took part in the research. The results would suggest that, when faced with such a situation, the objective working conditions interfere to such an extent that they have led university professors to develop behavioral patterns of acceptance, resignation, apathy and adaptation to the detriment of reflection, interest in new experiences and criticism of these same conditions. An increase in the burocratization of teaching activities, including what they consider to be the core of university teaching, research and extension, is closely connected to a kind of productivity demanded of professors. This has also been characterized as an obstacle to the freedom and emancipation, therefore, to the autonomy of professors.